2021
DOI: 10.48550/arxiv.2101.05474
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of resistivity on standing shocks in low angular momentum flows around black holes

Chandra B. Singh,
Toru Okuda,
Ramiz Aktar

Abstract: We study two dimensional low angular momentum flow around the black hole using the resistive magnetohydrodynamic module of PLUTO code. Simulations have been performed for the flows with parameters of specific angular momentum, specific energy, and magnetic field which may be expected for the flow around Sgr A*. For flows with lower resistivity η = 10 −6 and 0.01, the luminosity and the shock location on the equator vary quasi-periodically. The power density spectra of luminosity variation show the peak frequen… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…Now, the possible roles of the ADAF disk can i) produce weak intrinsic radiations (Bremsstrahlung and Synchrotron emission), and soft-excess (Compton thick/slim scattering) when R t < ∼ 100r g , ii) make barrier (centrifugal and pressure supported surface) for in-falling gas of the hot component flow, which can help in the jet generation or storage of the gas around the inner region of the disk or when preceding flow is compressed enough then the flow can make strong shock in the disk. Although, the shocks can be generated without the additional ADAF barrier as shown in many theoretical and numerical studies (Kumar & Gu 2018;Lee et al 2016;Garain et al 2020;Singh et al 2021), and the post-shock region is much hotter than other flows, which can produce very high energy radiations, like, hard X−ray, and soft γ−ray. This shock can be standing or quasi-steady or moving inward in accretion flow, and these kind of geometries is represented for the LHS and HISs.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Now, the possible roles of the ADAF disk can i) produce weak intrinsic radiations (Bremsstrahlung and Synchrotron emission), and soft-excess (Compton thick/slim scattering) when R t < ∼ 100r g , ii) make barrier (centrifugal and pressure supported surface) for in-falling gas of the hot component flow, which can help in the jet generation or storage of the gas around the inner region of the disk or when preceding flow is compressed enough then the flow can make strong shock in the disk. Although, the shocks can be generated without the additional ADAF barrier as shown in many theoretical and numerical studies (Kumar & Gu 2018;Lee et al 2016;Garain et al 2020;Singh et al 2021), and the post-shock region is much hotter than other flows, which can produce very high energy radiations, like, hard X−ray, and soft γ−ray. This shock can be standing or quasi-steady or moving inward in accretion flow, and these kind of geometries is represented for the LHS and HISs.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The generation of shock waves and oscillations is demonstrated using asymmetric hydrodynamical simulations (Lee et al 2011(Lee et al , 2016Das et al 2014). Singh et al (2021) recently have shown the production of shock with resistive MHD. However, the shock formation in these simulations is highly dependent on the initial conditions, and it requires supersonic injection of accretion materials at the outer boundary.…”
Section: Introductionmentioning
confidence: 99%
“…) With the most advanced generalrelativistic magneto-hydrodynamic (GRMHD) simula-tions, large numbers of studies have been performed to understand different kinds of flows (See for review Davis & Tchekhovskoy 2020;Mizuno 2022). In the last few decades, some efforts have been put to understand low-angular accretion flow in pseudo-Newtonian, axisymmetric (2D), hydrodynamic approach targeting formation of standing as well as oscillating shocks (e.g., Molteni et al 1994;Ryu et al 1995;Molteni et al 1996a,b;Lanzafame et al 1998;Proga & Begelman 2003;Chakrabarti et al 2004;Giri et al 2010;Okuda & Molteni 2012;Okuda 2014;Okuda & Das 2015;Okuda et al 2019;Singh et al 2021;Okuda et al 2022). However, so far, not much effort has been given to understanding low angular momentum flow in GRMHD framework which is related to multi-transonic accretion flows.…”
Section: Introductionmentioning
confidence: 99%